ART to prevent vertical transmission in Latin America: where are we in the “Treat‐All” era? - Gabriel Castillo‐Rozas M.D. Ph.D.; Fernanda F. Fonseca M.D.; Jessica Castilho M.D. M.P.H.; Peter F. Rebeiro Ph.D; Daisy M. Machado M.D. Ph.D.; Marco Tulio Luque M.D.; Emilia M. Jalil M.D. Ph.D.; Fernando Mejia M.D.; Ahra Kim M.P.H.; Bryan E. Shepherd Ph.D; Claudia P. Cortes M.D. (Journal of the International AIDS Society)
Abstract Introduction Antiretroviral therapy (ART) during pregnancy and at delivery has nearly eliminated vertical transmission (VT) in some settings but previously reported VT prevalence has been as high as 15% in Latin America and the Caribbean (LAC). We evaluated VT in the Caribbean, Central and South America network for HIV epidemiology to further study the benefit of ART on VT in our region. Methods We retrospectively collected data on cis‐gender women ≥15 years of age enrolled in HIV clinics in Brazil, Chile, Honduras and Peru from 2003 to 2018 with ≥1 pregnancy resulting in a live birth after clinic entry to examine the association of ART use at the time of delivery and VT. We used propensity‐score‐matched logistic regression to examine the odds of VT by ART use. Matching weights incorporated site, HIV RNA, CD4 cell count, maternal age, year and HIV diagnosis before or during pregnancy. We also examined the proportion of women who received ART during pregnancy before and after the treat‐all era, as defined within each country. Results A total of 623 pregnant women with HIV contributed 727 live births. Of all births, 613 (84.3%) infants had known HIV status and there were 22 (3.6%) VT events. Four of the 22 (18%) were born to women on ART at delivery, compared to 403 of 591 (68%) infants negative for HIV. In the propensity‐score‐matched model, ART use at delivery was associated with 85% decreased odds of VT (odds ratio = 0.15, 95% confidence interval 0.04−0.58). In the pre‐treat‐all era, 37% (181/485) of women received ART within 30 days of pregnancy diagnosis, compared to 59% (75/128) during the treat‐all era (p<0.001). In the pre‐treat‐all era, 4.3% (21/485) of infants were born HIV positive, compared to 0.8% (1/128) in the treat‐all era (p = 0.055). Conclusions We found a low prevalence of VT in our cohort, especially in the treat‐all era. ART use at delivery was strongly associated with a lower odd of VT. Despite improvements, access to ART during pregnancy remained far from universal. Therefore, new strategies to ensure its effective implementation in LAC are still warranted.